Manajemen Pemberdayaan OSIS dalam Pembentukan Karakter Kepemimpinan Siswa - Mujahidin Mujahidin; Siti Zuliani; Miftahul Ulum (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyse the empowerment management of the Intra-School Student Organisation (OSIS) in shaping student leadership character at MTs Miftahul Huda Silir Wates Kediri. This study stems from the importance of the role of OSIS as a strategic vehicle in developing the leadership potential of students based on Islamic values. The research uses a descriptive qualitative approach with subjects consisting of the head of the madrasah, OSIS advisors, and OSIS administrators. Data was collected through in-depth interviews, participatory observation, and documentation studies, then analysed using data reduction, data presentation, and interactive conclusion-drawing techniques to gain an in-depth understanding of the management practices applied.The results of the study indicate that OSIS empowerment in this madrasah is implemented through four main management functions, namely participatory planning, democratic organisation, experiential learning, and reflective evaluation oriented towards the formation of Islamic leadership character. The synergy between these functions produces a student leadership profile that is religious, disciplined, communicative, and responsible. Academically, this article contributes to strengthening the study of Islamic education management, particularly in the development of an Islamic leadership education model that integrates modern management principles and Islamic spiritual values. The results of this study can serve as a conceptual reference for Islamic educational institutions in designing strategies for empowering student organisations as effective, adaptive leadership laboratories rooted in transcendental moral values.